2014
DOI: 10.1016/j.leukres.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing risk of hypomethylating agent failure in patients with higher-risk MDS and practical management recommendations

Abstract: In Europe, azacitidine is the only hypomethylating agent approved for the treatment of patients with int-2-/high-risk myelodysplastic syndromes, offering significantly improved survival compared with conventional care. However, not all patients treated with azacitidine respond to treatment, and the vast majority of responders subsequently relapse. Currently, no standard care regimens have been established for patients after failure of azacitidine. Here, we discuss treatment options after loss of response or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 74 publications
(86 reference statements)
1
19
0
Order By: Relevance
“…However, this argument does not discount interrupted courses of therapy such as 5–2-2. Since the benefit of azacitidine has most definitively been demonstrated in RCT using the 7–0-0 schedule, it becomes important to collect efficacy data on the alternative dosing schedules in order to ensure they are at least as equally effective as 7–0-0 [ 7 ]. The objective of the current systematic review is to evaluate the efficacy and tolerability of the 5–0-0, 5–2-2, and 7–0-0 azacitidine dosing regimens in MDS patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, this argument does not discount interrupted courses of therapy such as 5–2-2. Since the benefit of azacitidine has most definitively been demonstrated in RCT using the 7–0-0 schedule, it becomes important to collect efficacy data on the alternative dosing schedules in order to ensure they are at least as equally effective as 7–0-0 [ 7 ]. The objective of the current systematic review is to evaluate the efficacy and tolerability of the 5–0-0, 5–2-2, and 7–0-0 azacitidine dosing regimens in MDS patients.…”
Section: Introductionmentioning
confidence: 99%
“…The classical response criteria (age, adverse cytogenetic, blast count) may only partially apply to HMA therapy. Several groups have also presented potential candidates as prognostic biomarkers, for example, data on HMA metabolism [18] or methylation profile [18, 95], but large scale validation of the prognostic value and accessibility of the techniques remain issues. The impact of mutational spectrum is also debated, with several groups showing that TET2, or DNMT3A mutated patients may have a higher probability of response [96].…”
Section: Expert Opinionmentioning
confidence: 99%
“…A large number of investigational agents are currently combined with HMA and investigated in clinical trials, but to date none has demonstrated improvements in outcome [16]. Following HMA failure, patients have poor prognosis and limited options [17], and there is no consensus on how to manage this patient population [18]. …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Consequently, it is strongly recommended to enroll patients with HMA failure in clinical trials. 17 Allogeneic stem cell transplantation, although potentially curative, is limited to a selected population based on criteria such as age and availability of donors. The availability of transplantation is also dependent on disease control, with a majority of patients requiring cytoreductive treatments prior to transplantation.…”
Section: Introductionmentioning
confidence: 99%